Broadband long wavelength infrared metamaterial absorbers - Yu Zhou; Zhongzhu Liang; Zheng Qin; Xiaoyan Shi; Dejia Meng; Lichao Zhang; Xiaoyi Wang (Results in Physics, 2020)
Infrared broadband absorbers are in great demand in various applications, such as integration into uncooled infrared detectors and microbolometers. In this thesis, we demonstrate and compare three different design methods: coupling multi-sized resonators, inlaying metallic structures in the dielectric layer and choosing laminated dielectric layers made of lossless and lossy materials. Due to their absorption mechanisms, we initially propose a W/ZnTe/W/Ge/W and an embedded Ti/Si/Ti absorber, both of which can achieve ultra-broadband absorption from 8 to 14 μm, with average absorptions of 88% and 92%. We further propose a Ti/Ge/Si3N4/Ti absorbers which can realise near-perfect absorption in the LWIR band, with average absorptions of 95% where all absorption curves exceed 90%. Our study provides the broadband LWIR absorbing structures in addition to providing new insight into the understanding of the interaction of propagating and localised surface plasmon resonances, with the prospect of expanding to other absorbing-structure designs from visible to THz regimes.